Negotiating exercise as medicine: Narratives from people with type 2 diabetes. (January 2021) - Stuij, Mirjam; Elling, Agnes; Abma, Tineke
The dominant notion that exercise is medicine puts a strong normative emphasis on individual responsibility for participation in sport and physical activity. The aim of this article was to explore how people with type 2 diabetes, a condition strongly linked to lifestyle behaviour both in origin and in management, translate this notion into their daily life. Based on a critical narrative analysis of stories of 18 Dutch people diagnosed with type 2 diabetes collected between 2012 and 2016, we found a range of meanings given to sport and physical activity. In addition, almost all respondents seemed to subscribe to the notion of exercise as medicine on a general level, either quite explicitly or in more subtle ways, for example, elicited by the interview setting. However, they employed different strategies to negotiate with the translation of this notion into their daily life, ranging from (almost) total acceptance to resistance. In addition, nearly all stories revealed mostly negative experiences with care and professional support regarding the uptake or continuation of sport or physical activity participation after diagnosis.